Reduced circulating endothelial progenitor cells in thromboangiitis obliterans (Buerger's disease). (December 2013) - Park, Hyung Sub; Cho, Kyung Hee; Kim, Koung Li; Kim, Duk-Kyung; Lee, Taeseung
To determine the role of endothelial progenitor cells (EPCs) in the pathogenesis of thromboangiitis obliterans (TAO), EPC numbers and colony-forming units, migratory function and tubular structure formation in vitro were compared between 13 young male TAO patients and two age-matched healthy control groups: 11 smokers and 12 non-smokers. TAO patients had significantly lower numbers of EPCs and EPC colonies compared to both non-smokers [190 (97.0–229) vs 528 (380–556), p < 0.001 for EPCs and 0.80 (0.53–1.00) vs 2.80 (2.08–4.00) per mm 2, p = 0.001 for EPC colonies] and smokers [190 (97.0–229) vs 272 (229–326), p = 0.012 for EPCs and 0.80 (0.53–1.00) vs 2.80 (1.80–3.93) per mm 2, p = 0.001 for EPC colonies]. However, there were no significant differences in migratory function or tube formation between the three groups. These results suggest that TAO patients have an intrinsic decrease in EPCs not entirely associated with smoking, which may be the cause of endothelial dysfunction seen in TAO patients leading to the development of this disease at early ages.